Caracterização química e atividade antibacteriana da pectina do noni (Morinda citrifolia L.) nativa e sulfatada - Pereira, Elaine Cristina (2015)
The noni (Morinda citrifolia L.) is a native shrub Southeast Asia adapted to dry and harsh environments. Its fruit proves to be a potential source of pectin. Pectin is a heteropolysaccharide present in vegetables, widely used by the food industry as a gelling agent, emulsifier, stabilizer and thickener. It has several biological properties, such as antibacterial activity, which can be enhanced by sulfation. The sulfation is characterized by the introduction of the sulfate group to the organic molecule, in order to enhance or develop new functional properties. In view of this, in order to provide another option in source of pectin and explore more the noni's potential, this research aimed to carry out the chemical characterization and evaluate the antibacterial activity of noni pectin before and after the sulfation process. The polymer was extracted at pH 4.0 from pulp of mature noni with 0.25% ammonium oxalate/oxalic acid. The sulphated derivative was produced by the chlorosulfonic acid-pyridine method. The native and sulfated pectins were characterized by infrared spectroscopy, thermal analysis, elemental analysis, gel permeation chromatography, quantification of protein and as to the rheological behavior and zeta potential. The antibacterial activity was evaluated against Gram positive bacteria (Listeria monocytogenes and Staphylococcus aureus) and Gram negative (Escherichia coli, Pseudomonas aeruginosa and Salmonella Enteritidis) by a microdilution broth assay (2 to 10 mg/mL). Noni pectin showed slightly yellowish color, low degree of esterification (38.34%) and high molar mass (222.82 kg/mol). The sulfation was satisfactory, being confirmed by infrared spectroscopy (bands at 829 and 1247 cm-1 associated with the sulfate groups) and elemental analysis (%Sulphur: 12.51). This modification resulted in changes in the properties of pectin, such as increase of thermal stability and electronegative character; reduction of the molecular weight and viscosity. The native and sulfated pectins exhibited antibacterial action. The native polymer was more effective and produced inhibitions around 80 and 83% compared to E. coli and P. aeruginosa, respectively, to 10 mg/mL. The sulfated pectin showed lowest activity, with higher inhibition rates obtained at 10 mg/mL for L. monocytogenes (26.45%), S. aureus (26.25%) and P. aeruginosa (28.39%). We conclude that the fruit of noni is a potential source of pectin, with yields similar to industrial sources (~15%). The sulfation negatively affected the antibacterial action of pectin, causing losses in its inhibitory activity.